Pengaruh Konsentrasi Ekstrak Etanol Daun Salam (Syzygium Polyanthum (Wight) Walp.) Terhadap Pertumbuhan Bakteri Aggregatibacter Actinomycetemcomitans Dominan Periodontitis In Vitro - Saleha, Junita Ratu, drg. Mahmud Kholifa, MDSc, drg. SE Yuletnawati, MDSc (2015)
Periodontitis is an inflammatory disease on the supporting tissues of the teeth that caused by Aggregatibacter actinomycetemcomitans (Aa), that leads to destructive tissue damage. Therapies that can be done to inhibit the growth of bacteria that cause periodontitis are plaque control, scaling, root planning, and antibiotics. Syzygium polyanthum (Wight) Walp ethanolic extract is natural ingredient that can be used as antibacterial ingredient. This research was conducted to examine concentration effect of Syzygium polyanthum (Wight) Walp ethanolic extract on the growth of Aggregatibacter actinomycetemcomitans in vitro and to figure out what concentration of Syzygium polyanthum (Wight) Walp ethanolic extract is the most potential in hindering the growth of Aggregatibacter actinomycetemcomitans. The method used in the antibacterial test was diffusion method. Syzygium polyanthum (Wight) Walp that had been through determination test were later extracted with maceration method using ethanol 70%. This study was divided into 7 treatment groups and 3 times of replication. Each of the treatments consisted of Syzygium polyanthum (Wight) Walp ethanolic extract of 2.5%, 5%, 10%, 20%, 40%, aquades as negative control, and tetracycline as positive control. Data obtained were analyzed with one way ANOVA test with significance rate 95% (α = 0,05) then continued with Post Hoc LCD test. The average diameters of inhibition zone from Syzygium polyanthum (Wight) Walp ethanolic extract of 2.5%, 5%, 20%, 30%, 40%, aquades, and tetracycline were respectively 9.52; 11.2; 12.31; 13.53; 14.34; 0; and 20.67 mm. The result indicated probability value 0,000 (p < 0,05) which means that there were some significant differences between each treatment groups. Concentration of Syzygium polyanthum (Wight) Walp ethanolic extract that is most potential in hindering the growth of Aggregatibacter actinomycetemcomitans is the concentration of 40%.